UPAYA PENCEGAHAN VIRUS COVID-19 MELALUI PENGABDIAN MASYARAKAT MAHASISWA KKM KELOMPOK 12 DI KELURAHAN BENDUNG KECAMATAN KASEMEN 2021 - Muhammad Ichwanul Yususp; Ina Rohiyatussakinah; Kristina Sri Prihatin (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Health is currently an important thing, but there are still many people who don't care. Even though we take care of our health, then other things will also have an effect. For example, the fields of education, economy, trade, and so on. In this case, students do their service in the form of KKM held by the University. This KKM service aims to provide knowledge to the community as the implementation of knowledge from the academic environment. Three things that are the targets of this program are the eradication of illiteracy, agricultural counseling on pest eradication and the provision of trash bins as a form of concern for environmental cleanliness. With this student work course KKM, it is hoped that the community will be aware of health, education, and survival.